1986
DOI: 10.1104/pp.80.1.277
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Phytoalexin Pisatin by a Methyltransferase from Pea

Abstract: Previous labeling studies in vivo suggest that the terminal step of (+)pisatin biosynthesis in Pisum sativum L. is methylation of the phenol (+)6a-hydroxymaackiain (HMK). We have found that extracts from pea seedlings perform this reaction, using S-adenosylmethionine as the methyl donor. The enzyme activity was induced by microbial infection or treatment with CuC12, which elicit pisatin synthesis, though some activity was also present in healthy tissues. It has been reported that CuCl2-treated pea tissue provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
2

Year Published

1988
1988
1994
1994

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 19 publications
0
16
0
2
Order By: Relevance
“…Furthermore, HMKMT exhibited a low Km for (+)HMK. These facts, combined with the observation that it is induced by treatments which elicit pisatin synthesis (23), suggest that the enzyme we purified is induced specifically as part of the phytoalexin response.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Furthermore, HMKMT exhibited a low Km for (+)HMK. These facts, combined with the observation that it is induced by treatments which elicit pisatin synthesis (23), suggest that the enzyme we purified is induced specifically as part of the phytoalexin response.…”
Section: Discussionmentioning
confidence: 60%
“…The reaction was stopped with 350 ,uL 0.3 M sodium citrate (pH 4) and 4.5 mL of 0.55% PPO in toluene. The two phase system was agitated in a vortex mixer, and the content of nonpolar radioactivity was measured directly by scintillation counting (23). One unit of enzyme activity (1 kat) was the amount producing 1 mol of pisatin per s under these conditions.…”
Section: Methyltransferase Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Severa1 lines of evidence suggested that CHS was synthesized in root tissue: root tissue treated with CuCI, synthesizes pisatin (Banks and Dewick, 1982;Sweigard, Matthews, and van Etten, 1986), and the expression of nodulation-specific genes in Rhizobium is induced by flavones and flavanones extracted from pea roots (Firmin et al, 1986;Peters et al, 1986;Redmond et al, 1986). Preliminary induction time course experiments were carried out to optimize for CHS mRNA expression in CuCI,-induced roots.…”
Section: Results Lsolation Of Chalcone Synthase Cdnasmentioning
confidence: 99%